Effect of irrigation frequency on cocoa (Theobroma cacao L.) bean quality in Ghana’s major production zone (International Journal of Agricultural Research, Innovation and Technology, 2026)
The productivity and quality of cocoa, a key economic crop in Ghana, are increasingly threatened by erratic rainfall and climate variability. This study investigates how different irrigation frequencies affect cocoa bean quality across three major production regions in Ghana: Western, Central, and Eastern. The study adopts a field-based experimental design assessing three irrigation regimes: morning, evening, and every two days. Key quality parameters evaluated included bean count, moisture content, and purity levels. Standardized post-harvest processing and laboratory techniques were employed, and data were analysed using ANOVA with Tukey’s test for mean separation at p < 0.05. Results showed that irrigation frequency significantly influenced bean count and purity levels, with notable regional variations. In the Western Region, morning irrigation yielded the highest bean count (125.7) and purity (97.77%). Conversely, in the Central Region; evening irrigation produced the highest bean count (113), while in the Eastern Region; a two-day interval gave the highest count (122). Moisture content remained relatively stable (6.8–7.2%) across treatments and regions, indicating that post-harvest drying practices were effectively managed. However, purity decreased with increased irrigation frequency, highlighting a trade-off between yield and quality under intensive watering. These findings suggest that optimising irrigation schedules based on regional agro-climatic conditions can significantly improve cocoa yield without compromising quality. The study underscores the need for climate-adapted irrigation strategies and offers data-driven insights for resource allocation in Ghana’s cocoa sector. It also highlights the importance of integrating quality-focused irrigation management into broader climate resilience and sustainable cocoa production frameworks. This research provides a practical foundation for policymakers, cocoa extension officers, and farmers seeking to enhance cocoa quality and market competitiveness under water-scarce conditions.Int. J. Agril. Res. Innov. Tech. 15(2): 98-106, Dec 2025